Icaritin suppresses development of neuroendocrine differentiation of prostate cancer through inhibition of IL-6/STAT3 and Aurora kinase A pathways in TRAMP mice - Sun, Feng (OXFORD UNIV PRESS, 2021)
10.1093/carcin/bgw044